Compete: Urban Land Institute | Gerald D. Hines student urban design competition - Perry, John (Kansas State University, 2009)
The Urban Land Institute / Gerald D. Hines Student Urban Design Competition offers teams of multi-disciplinary graduate students the opportunity to address a large scale site that presents complex challenges requiring practicable, innovative solutions reflecting responsible land use. Solutions must incorporate design, planning, market potential, market feasibility, and development. Some of the brightest students from universities across the United States and Canada compete annually, incorporating bold ideas, outstanding graphics, and great presentations in order to win the competition. The scale of the competition and the quality of entries makes it difficult to advance from the initial submission round to the final four entries selected for the final phase of the competition. Entering the competition is a complex process requiring adherence to a multitude of rules and regulations about team formation, design solutions, financial information, presentation materials, and deadlines. This study documents the process of one student team entering the 2009 competition. Analysis of previous competition responses and principles of urban design theory informed an innovative design solution that incorporates sustainability, livability, and connectivity. This project analyzes previous project entries, looking for patterns and indicators to guide the competition response. Combining the analysis and design philosophy, which utilizes specific sustainable landscape architectural principles, forms the framework of the design solution. The response focuses on process-driven design implementing sustainable frameworks that account for existing an emergent ecologies, historical and cultural relevance, energy efficiency, hydrological patterns, and public transportation. Results of the study led to conclusions regarding team organization, teamwork, graphic composition, and presentation that will be beneficial for future competition entrants.
Keywords: Compete; Urban Land Institute; Urban Design Competition; Gerald D. Hines; John Perry; Landscape Architecture; Architecture (0729); Landscape Architecture (0390); Urban and Regional Planning (0999)